Analisis Normatif Perlindungan Hukum Terhadap Anak Sebagai Korban Kejahatan Pedofilia - Widhy Andrian Pratama (Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research aims to find out briefly and simply about legal protection for children as victims of pedophilia crimes. The research method used in this research is: normative legal research. which essentially means that there has been a gap between das sollen and das sein at the level of norms or legal rules that apply in society. so that the law we aspire to cannot function as it should. From this research we can conclude that. Very firm and harsh action is needed in imposing criminal sanctions on perpetrators of pedophilia crimes because they have damaged and taken away the future of the nation's generation. The criminal sanctions can have a deterrent effect and provide healing and treatment for the mental and sexual sexuality of the perpetrator. Keywords: Children, Crime Victims, Pedophelia.